Seismic response modification factor for steel slit panel-frames. (15th February 2019) - Aliakbari, Fatemeh; Shariatmadar, Hashem
Highlights: Correct steel slit panels modeling in finite element software (Abaqus). Overstrength factor of dual moment-resistant frame with steel slit panel is 4.16. Reduction factor due to the ductility for this system is 1.91. Response modification factor (behaviour factor) for this system is 8.11. Overstrength factors decrease up to 6 story and keep unchanged for higher structures. Ductility factors decrease up to 10 story and keep unchanged for higher structures. Behaviour factors decrease up to 10 story and keep unchanged for higher structures. Abstract: In this paper, the overstrength, ductility and response modification factors of moment resistant frame (MRF) with steel vertical slit panel (SSP-MRF) were investigated and determined. For this purpose, buildings with various stories were used. Abaqus software was used to perform the static pushover analysis, linear dynamic analysis, and nonlinear incremental dynamic analysis. In this research, seismic response modification factor has been evaluated for each model structure using pushover analysis, and the tentative value 8.11 has been proposed for the ultimate limit state design method. Some of the results of pushover analysis and nonlinear incremental dynamic analyses were compared. According to this comparison, the response modification factor of 10-story model structure derived from pushover analysis (6.14) was slightly smaller than those obtained from incremental dynamic analyses (7.5).